Diagnostic traits of medicinal herbal raw material of species of Thymus genus - M. R. Hrytsyna; M. I. Skybitska; О. Т. Novikevich (Regulatory Mechanisms in Biosystems, 2022)
The paper presents the peculiarities of morphological-anatomical structure of the organs, which are diagnostic traits of herbal raw materials (HRM) of the commonest species of Thymus L. genus in the moderate climatic zone. We determined that the studied species develop a subshrub life form, which grows monopodially in Th. pulegioides and Th. marschallianus, and sympodially with mono-, di- and polycyclic types of monocarpic shoots in Th. serpyllum. Inflorescence is of thyrsoid type with opposite partial inflorescences, which are constituents of simple dichasia with monochasia. Macroscopic and microscopic diagnostic features of the HRM are structure and pubescence on the stem, leaves and flowers, the anatomical structure of which was studied on 20 µm thick transversal sections using a light microscope. In Th. pulegioides, stems are tetrahedral, pubescent on ribs with unicellular and two-cellular elbow-shaped hairs. Leaves are ovoid, covered by multiangular epidermis that bears diacytic stromas, sharpened capitate unicellular and two-cellular hairs and 10–12 cellular essential oil glandules. In Th. marschallianus, the stems are poorly tetrahedral, rounded, pubescent on the entire surface. Leaves are elliptic, the cells of the epidermis are elongated, significantly tortuous, with 10–12 cellular glandules, diacytic stromas, capitate and unicellular hairs. In Th. serpyllum, the stems are cylindric, pubescent all round. The leaves are elongated-elliptic, epidermis cells are oval, tortuous, stromas are diacytic, essential oil glandules are 8–10 cellular, number of papilla-like hairs is low. The petioles and lamina base of the studied species are pubescent on the sides with short, coned and elbow-shaped, 2–3 cellular hairs, among which there are long, 4–8 cellular hairs; the hairs in Th. serpyllum are multicellular, interrupted. In mesophyll, there are schizogenous essential oil reservoirs. In Th. marschallianus and Th. pulegioídes, the calyx is campanulate, bilabiate, and pubescent. The flower corolla is purple-violet, bilabiate, has tube and outward bend, pubescent inside with coned unicellular hairs, has essential oil glandules and glandular capitate hairs, and pubescence in the fauces comprises long unicellular hairs. In Th. pulegioídes, cells of the corolla epidermis are multiangular-shaped with insignificantly wavy walls, in Th. marschallianus ‒ rectangular with significantly wavy walls. Cells of the tube epidermis are rectangular, tortuous. Surface of the corolla of Th. serpyllum is pubescent on both sides with short, cone-like and three-cellular, interrupted hairs, and also capitate hairs, and has essential oil glandules. Epidermis cells are multi-angular, tubes – rectangular and narrow. The obtained results may be used for diagnostics of HRM of morphologically similar species during their preparation.